The Role of Organizational Culture in Improving the Green Supply Chain: An Exploratory Research in Al-Ittihad Food Industries Company Limited (Czech Journal of Multidisciplinary Innovations, 2024)
The Research Aims To Identify The Role Of Organizational Culture In Improving The Green Supply Chain Of The Union Company For Food Industries In Babil Governorate, And In Order To Achieve This, The Dimensions Of Organizational Culture (Relationships, Goals, Rewards) Were Adopted, And The Dimensions Of The Green Supply Chain (Purchase) Were Adopted. Green, Green Manufacturing, Green Marketing, Green Design), And Al-Ittihad Company For Food Industries Limited Was Chosen As One Of The Largest Food Industry Companies In Iraq As An Exploratory And Analytical Field For Research By Distributing A Questionnaire That Included (78) Respondents From The Administration Managers, Heads Of Departments, Divisions And Their Units For Factories The Research Sample, And One Of The Most Important Conclusions Reached By The Research Is That The Organizational Culture Effectively Affects The Promotion Of The Green Supply Chain Of The Organization. The Research Sample In Light Of The Great Competition In The Food Industry Sector In Iraq. Organizational In Enhancing The Positive Impact Relationship Between It And The Dimensions Of The Dependent Variable Of The Green Supply Chain Within The Industrial Sector And In Line With Continuing To Create Products Of Strategic Value For Industrial Enterprises And Achieving Environmental Sustainability By Keeping Abreast Of Developments And Seizing Opportunities To Ensure Continuity, Growth And Survival In The Labor Market.